PENGARUH SIZE, NPL, EQUITY TO ASSET RATIO, LDR, GWM, LABOR PRODUCTIVITY DAN MARKET CONCENTRATION TERHADAP KINERJA BANK (Studi pada Bank Umum Konvensional yang Terdaftar di BEI Tahun 2014-2018) - rochmad kristiawan; Prasetiono Prasetiono (JURNAL STUDI MANAJEMEN ORGANISASI, 2020)
The existence of different levels of bank’s performance in each Indonesian banks and the existence of banks with under level performance makes research on the factors that influence bank’s performance becomes more important to be examined. The aim of the research is  to analyze the effect of size, size, Non-performing Loan (NPL), Equity to Asset Ratio (EAR), Loan to Deposit Ratio (LDR), reserve requirement (GWM), labor productivity and market concentration (which is proxied by market share of each bank) on the performance of listed conventional banks in Indonesia. The bank’s performance in this research is measured by Return on Asset (ROA).The research sample used are 25 listed conventional banks in Indonesia for the 2014-2018 period. The data selection method used in this research is purposive sampling method. The hypothesis testing of this study using multiple linear regression analysis with SPSS 26 program.The study found that size, Equity to Asset Ratio (EAR), labor productivity and market share have a significant positive effect on bank’s performance. Non-performing Loan (NPL) have a significant negative effect on bank’s performance. Loan to Deposit Ratio (LDR) and Reserve requirement (GWM) have a positive but not significant effect on bank’s performance